(untitled) (Research, Society and Development, 2021)
In obesity, there is an excess of fat, which can be localized or not, and this condition can cause damage to health. This excess leads to the occurrence of cardiovascular disease, diabetes, cancer, kidney disease. To assess its occurrence, this study evaluated issues related to overweight and obesity in people assisted by an Integrated Health Action (AIS) in three municipal schools in Santarém-Pará. This is a descriptive research, with a quantitative approach that followed the method described by Charles Maguerez’s Diagram, taking place in five stages: observation of reality, key points, theorization, solution hypothesis and application to reality. Data were obtained through anthropometric assessment, using the variables: body mass and height, and application of a socioeconomic questionnaire. Eighty-one people comprised the study sample. The results show that 32 people are overweight, 30 obese, 1 underweight and 18 with normal parameters, whereas most respondents stated that they had a family income of up to two minimum wages, corresponding to 69.23% men and 52.73% women. given these results, new studies should be carried out that can expand the sample, and thus have more significant data on this reality, and from such information can be included in the strategic planning of primary care, preventive actions, which contribute to the reduction of overweight and obesity rates.